2016
DOI: 10.1016/j.scitotenv.2016.01.110
|View full text |Cite
|
Sign up to set email alerts
|

An index for estimating the potential metal pollution contribution to atmospheric particulate matter from road dust in Beijing

Abstract: • An innovative road dust index was developed.• Road dust characteristics were ranked and weighted in the index model.• Source and transport factors were both considered in the index model. The resuspension of road dust from street surfaces could be a big contributor to atmospheric particulate pollution in the rapid urbanization context in the world. However, to date what its potential contribution to the spatial pattern is little known. Here we developed an innovative index model called the road dust index (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Resuspension of road dust is an important source of atmospheric particulate matter, particularly in the 2.5µm fraction (PM 2.5 ) [ 5 , 6 , 7 ]. Resuspended road dust from paved and unpaved roads has been considered a significant contributor to PM 10 and PM 2.5 particularly in urban areas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resuspension of road dust is an important source of atmospheric particulate matter, particularly in the 2.5µm fraction (PM 2.5 ) [ 5 , 6 , 7 ]. Resuspended road dust from paved and unpaved roads has been considered a significant contributor to PM 10 and PM 2.5 particularly in urban areas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported by an earlier study road dust resuspension has been responsible for PM 10 , PM 2.5 , and PM 1 , respectively, for an average of 37 percent, 15 percent, and 3 percent of total traffic emissions [ 9 ]. Early studies suggested that particles of road dust with sizes below 100 μm can be readily resuspended by passing vehicles or wind [ 7 ]. Pollution from particulate matter has been considered a serious threat, especially for cities with heavy traffic [ 2 ], which is responsible for generating numerous metals like Fe, Cu, Zn, Sb, and Pb through exhaust and non-exhaust emissions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human activities result in environmental pollution, for example, through the release of various toxic metals containing copper, lead, cadmium, and arsenic to urban environments (1). The dust of the street is composed of solid particles deposited on the surface of the ground, which acts as a reservoir for the collection of short-lived environmental materials from the surrounding areas (2,3). The concern about the problem of metal pollution in street dust in recent decades has increased and research efforts have been correspondingly increased on the issue.…”
Section: Introductionmentioning
confidence: 99%
“…Serbian spruce, Picea omorika is an ancient endemic species found in natural communities in Central Europe (Bugała 2000). Now, atmospheric and soil pollution constitutes a major problem especially in urban environment (Parzych and Jonczak 2014;Świercz et al 2014;Chen et al 2016;Zhao et al 2016). Monitoring the quality of the environment using trees is widely accepted as a reliable and inexpensive way of obtaining information about the state of the environment.…”
Section: Introductionmentioning
confidence: 99%